2021
DOI: 10.1016/j.adro.2021.100690
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Retrospective Analysis of the Outcomes of Proton Beam Therapy for Patients With 1 to 3 Pulmonary Oligometastases From Various Primary Cancers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The analysis of the cohort study data set of PT showed durable LC (3-year LC, 83.2%) and OS (3-year OS, 68.1%) with an acceptable risk of grade ≥ 3 toxicity (incidence rate, 0.8%) in metastasis-directed therapy for P-OM. This result corresponded with the results of previous reports on PT for P-OM [ 16–18 ]. The range of the prescribed dose in this cohort series was relatively wide because the prescribed doses depended on the physician’s decisions, based on the size, number and location of a target, surrounding organs at risk (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The analysis of the cohort study data set of PT showed durable LC (3-year LC, 83.2%) and OS (3-year OS, 68.1%) with an acceptable risk of grade ≥ 3 toxicity (incidence rate, 0.8%) in metastasis-directed therapy for P-OM. This result corresponded with the results of previous reports on PT for P-OM [ 16–18 ]. The range of the prescribed dose in this cohort series was relatively wide because the prescribed doses depended on the physician’s decisions, based on the size, number and location of a target, surrounding organs at risk (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…S1 ). In total, five relevant studies on X-SBRT [ 11–15 ] and three relevant studies on PT [ 16–18 ] were identified ( Table 3 ). Different studies had different inclusion criteria, characteristics of patients and primary cancers, and treatment protocols.…”
Section: Resultsmentioning
confidence: 99%
“…The OS rates are comparable to those of lung resection (one-year OS rates: 60%-100%, two-year OS rates: 36%-100%, three-year OS rates: 40.2%-60%) in previous reports [ 6 - 11 ]. A Japanese nationwide multi-institutional retrospective analysis of PBT for one to three lung oligometastases from various cancers reported one-, two-, and three-year LC rates of 92.2%, 86.3%, and 78.4%, respectively [ 16 ]. Local treatment results for lung metastases of esophageal cancer are summarized in Table 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated the absence of grade 3 or higher AEs. A previous study on PBT for lung oligometastases in various primary cancers reported seven patients with grade 2 AEs (5.9%) and one with grade 3 AEs of radiation dermatitis (0.8%) [ 16 ]. In a study on lung oligometastases in esophageal cancer, three (3.3%) patients had grade 2 AEs, four (4.4%) had grade 3 or higher AEs, and one (1.1%) had grade 5 radiation-induced pneumonitis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…79 Owing to its physical properties, PBT can deliver an ablative dose with minimal increase in risk of complications in many cases, PBT can provide opportunities for curation in oligometastatic HCC patients. 80 Further investigation to evaluate the efficacy of PBT would be worthwhile.…”
Section: Future Perspectivesmentioning
confidence: 99%